A case of severe thrombocytopenia after the first exposure to rifampicin. (2023) - Nakane, Chinatsu; Nishimoto, Koji; Kishimoto, Ei; Suzuki, Kosuke; Nakagawa, Emiko; Morikawa, Moeko; Murakami, Yurina; Aoshima, Yoichiro; Matsushima, Sayomi; Harada, Masanori; Uto, Tomohiro; Imokawa, Shiro
Abstract: Severe immune thrombocytopenia is a rare side-effect of rifampicin (RFP) and can be life-threatening. Here, we report the case of a 74-year-old male with tuberculous pleurisy who developed severe thrombocytopenia after first exposure to RFP. Platelet count decreased to 1 × 10 3 /μL after 7 days of treatment with RFP, isoniazid, ethambutol, and pyrazinamide. After all the drugs were discontinued, the platelet count recovered. As thrombocytopenia did not occur after re-administration of drugs other than RFP, the patient was diagnosed with RFP-induced thrombocytopenia. Clinicians should be aware that RFP can induce acute and severe thrombocytopenia even without previous exposure to this drug.